Ordinary goodness for ordinary people: an essay on the Kantian system - Shapiro, JD (2020)
Kant does not explicitly present an account of what one might call ordinary goodness for ordinary people, or the sense of moral worth one has in mind when one judges someone to be a “good person”: somewhat worryingly, when he does discuss the moral worth of people in Religion Within the Boundaries of Mere Reason, he seems to stray very far from terms which can apply to ordinary people in their everyday lives. Indeed, there is a plausible line of reasoning that owing to, first, Kant’s thoroughgoing determinism and, second, his complete rejection of compatibilist conceptions of freedom, Kant cannot take ordinary people to be free and, as a result, morally responsible—a fortiori, he cannot have an account of ordinary goodness for ordinary people. I find that, ultimately, Kant can reject such reasoning through what I call his doctrine of Transcendental Compatibilism, which consists of three claims: (i) due to Transcendental Idealism, Kant’s determinism is compatible with a certain libertarian-style freedomcalled transcendental freedom; (ii) transcendental freedomis precisely that kind of freedom required for moral responsibility according to Kant’s moral theory, and; (iii) ordinary human beings actually are, under normal circumstances, transcendentally free and, as such, are morally responsible despite living in a deterministic world. By understanding this doctrine, one can derive an account of phenomenal moral worth—i.e., ordinary goodness for ordinary people—from Kant’s comments on noumenal moral worth. Therefore, in Chapter I, I explore Kant’s determinism and, through examining his resolution to the Third Antinomy of the first Critique, establish (i) above; in Chapter II, I examine the core of Kant’s moral theory, establish (ii) and (iii) above, and respond to three potent objections; finally, in Chapter III, I elucidate Kant’s account of noumenal moral worth so to derive a positive characterization of phenomenal moral worth—i.e., a Kantian account of ordinary goodness for ordinary people—therefrom.